2018
DOI: 10.1590/1414-431x20187526
|View full text |Cite|
|
Sign up to set email alerts
|

Participation of hepatic α/β-adrenoceptors and AT1 receptors in glucose release and portal hypertensive response induced by adrenaline or angiotensin II

Abstract: It has been previously demonstrated that the hemodynamic effect induced by angiotensin II (AII) in the liver was completely abolished by losartan while glucose release was partially affected by losartan. Angiotensin II type 1 (AT1) and adrenergic (∝1- and β-) receptors (AR) belong to the G-proteins superfamily, which signaling promote glycogen breakdown and glucose release. Interactive relationship between AR and AT1-R was shown after blockade of these receptors with specific antagonists. The isolated perfused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…We further supported this hypothesis by supplementing with AD and antagonizing α- or β-adrenergic receptors. Antagonists of α-adrenergic receptors are often used in the treatment of hypertension and urinary retention, work in the peripheral vasculature and inhibit the uptake of catecholamines in smooth muscle cells, resulting in vasodilation and blood pressure lowering [ 32 ]. Additionally, β-adrenergic receptors have often been researched in antihypertensive treatment [ 33 ], energy metabolism regulation [ 34 ], cardiovascular disease treatment [ 35 ], and anticancer treatment [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…We further supported this hypothesis by supplementing with AD and antagonizing α- or β-adrenergic receptors. Antagonists of α-adrenergic receptors are often used in the treatment of hypertension and urinary retention, work in the peripheral vasculature and inhibit the uptake of catecholamines in smooth muscle cells, resulting in vasodilation and blood pressure lowering [ 32 ]. Additionally, β-adrenergic receptors have often been researched in antihypertensive treatment [ 33 ], energy metabolism regulation [ 34 ], cardiovascular disease treatment [ 35 ], and anticancer treatment [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of arrhythmia is complicated. Molecular biology studies have revealed cardiac autonomic nerve dysfunction, such as excitement of the vagus nerve and inhibition of sympathetic nerves (de Araújo et al, 2018;Janssens and Michels, 2019). Abnormal structure and function of ion channels can cause arrhythmia (Torrente et al, 2020).…”
Section: Introductionmentioning
confidence: 99%